THE EFFECT OF FOOD ADDITIVES ON PALM MUSHROOMS (VOLVARIELLA VOLVACEA) MEATBALLS AND MOCAF FLOUR (MODIFIED CASSAVA FLOUR) - Ota, Muhammad; Prasetya, Andwini; Moulina, Methatias Ayu; Darius, Darius (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to characterize the effect of food additives on the quality of meatballs made from palm mushrooms (Volvariella volvacea) and mocaf flour. Meatballs were made with a formulation of 70% palm mushrooms and 30% mocaf, and the addition of carrageenan, CMC, and STPP at concentrations of 0.25%, 0.5%, and 1% with 9 treatments. The parameters analyzed included yield, water content, protein, fiber, organoleptic and production cost. The results showed that the yield ranged from 82.15–96.39% and was significantly different between treatments. Water content was 65.01–70.60%, while the highest protein and fiber content was obtained with the addition of 0.25% carrageenan, respectively 10.53% and 7.97%, respectively. The type and concentration of food additives significantly affected the yield, water content, protein, fiber and texture but did not significantly affect the color and taste of palm mushroom and mocaf flour meatballs.